If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying log(sub + -2)(64) = x Reorder the terms: glo(-2 + bsu)(64) = x Reorder the terms for easier multiplication: 64glo(-2 + bsu) = x (-2 * 64glo + bsu * 64glo) = x Reorder the terms: (64bglosu + -128glo) = x (64bglosu + -128glo) = x Solving 64bglosu + -128glo = x Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '128glo' to each side of the equation. 64bglosu + -128glo + 128glo = 128glo + x Combine like terms: -128glo + 128glo = 0 64bglosu + 0 = 128glo + x 64bglosu = 128glo + x Divide each side by '64glosu'. b = 2s-1u-1 + 0.015625g-1l-1o-1s-1u-1x Simplifying b = 2s-1u-1 + 0.015625g-1l-1o-1s-1u-1x Reorder the terms: b = 0.015625g-1l-1o-1s-1u-1x + 2s-1u-1
| -25/-10.5 | | -15y-10y=-10.5 | | 3q-7(5-8q)= | | -132(n+9)= | | 4y=-4x-4 | | 2y=-6x-24 | | 8g+4+5g=-5 | | m+7m-5m-5= | | 20.00-1.45d=1.15 | | -11x-4= | | log^2(64)=x | | h=-16t^2+12x+10 | | 4.28-0.4d=1.48 | | x+1/2*x/2=50 | | 0.4x-2.3=0.5 | | 2z/2=4/2 | | x^2-5x-8=x | | -3(p-7)= | | x^-3/36x^-4 | | -5=9z+6 | | -x+1=27 | | 5y+2(y-6)=(y+1)-4 | | 7y+3(y-3)=5(y+1)-2 | | -6Y=(-110X/7)+80 | | 7.88=2*3.14r | | -16+(6x-4)=6 | | -16+(6x+4)=6 | | -3(r-4)= | | 20.3x=20(x+.0030) | | 63-6y=52+16y | | 5x-26=4(5+7x) | | -x-6/7y=-4/7 |